Internal locus of control dan kemampuan manajemen waktu dengan prokrastinasi akademik pada mahasiswa skripsi - Lea Marsita Sari; Niken Titi Pratitis; Asti Haryanti (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2022)
The tendency of academic procrastination can have a negative impact on students, which results in assignments not being completed optimally and even being late in the deadline for submission. This study aims to determine the relationship between internal locus of control and time management skills with academic procrastination in students who are taking thesis at the Faculty of Psychology. This study uses quantitative research methods, the subject is 103 students of the Faculty of Psychology who take the script. Hypothesis testing using multiple regression analysis, the results of the first hypothesis test showed that the internal locus of control variable had no significant effect on the tendency of academic procrastination. The results of the second hypothesis test show that time management skills have a significant effect on the tendency of academic procrastination. The results of the third hypothesis test show that internal locus of control and time management skills are jointly significantly related to academic procrastination. Internal locus of control and time management skills together contributed 60.4% related to academic procrastination.